Memotret Tata Kelola Masjid: Studi Kasus pada Masjid Agung Nurul Iman dan Masjid Taqwa Muhammadiyah Sumatera Barat - Ilahia, Nesi; Ihsan, Hidayatul; Atsarina, Alyani (Universitas Negeri Padang, 2026)
Mosques are not merely places of worship but also serve as social institutions that need professional and accountable management of their financial and organizational resources. As most of the resources come from congregational donations, applying Good Mosque Governance becomes crucial to maintain transparency, accountability, responsibility, independence, and fairness. This study explores the implementation of Good Mosque Governance principles at Nurul Iman Grand Mosque and Muhammadiyah Taqwa Mosque in West Sumatra. A qualitative case study approach was used, guided by Stewardship Theory. Findings indicate that both mosques have generally applied the principles of good governance, though some managerial and documentation challenges still exist. The findings further show that the implementation of these principles is associated with more structured management practices, clearer financial accountability, and higher levels of perceived trust among congregants. Future studies are encouraged to explore broader models of mosque governance that integrate digital transparency and inter-organizational collaboration.